People’s perception on animal welfare: why does it matter? - De la Fuente, María Fernanda; Souto, Antonio; Caselli, Christini; Schiel, Nicola (Ethnobiology and Conservation, 2018)
Understanding peoples’ perception on animal welfare is vital to promote people awareness and changes in attitudes towards this subject. Here we present a short review on public perception of animal welfare in different instances and the factors influencing each one of them. While the great public concern towards farm and laboratory animals resulted in increased efforts to assess animal welfare in these instances, less attention has been given to pets, captive wild animals and their use for entertainment purposes. Irrespective of the instance under consideration, public perception on animal welfare depends on a myriad of biological and sociocultural factors, ranging from people’s gender and age to their own experiences and values. The knowledge on people’s perception will help to refine the message to different audiences, which in turn may increase the pressure on decision-makers to promote positive welfare in animals.